GASTROINTESTINAL BLEEDING WITH NEW ORAL ANTICOAGULANTS: EPIDEMIOLOGY, RISK FACTORS, TREATMENT AND PREVENTION (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Conclusion: One of the problems of emergency surgery that has not been sufficiently resolved so far is the issue of timely diagnosis and treatment tactics of bleeding from the gastrointestinal tract. At the same time, bleeding from stomach and duodenal ulcers is increasing day by day and is currently 90-103 people per 100,000 people [Abdullaev A.N., Litvinova D.V., 2018]. Currently, bleeding due to gastric and duodenal ulcers has doubled, especially in the elderly and elderly. Mortality from acute bleeding due to wounds from the gastrointestinal system is 5-20%, after emergency operations it is 4-73%, and in the elderly, this indicator is higher than 80% [Eremeev A.G., 2018].